2016
DOI: 10.1097/sla.0000000000001481
|View full text |Cite
|
Sign up to set email alerts
|

Long-term Quality of Life After Distal Subtotal and Total Gastrectomy

Abstract: Although 5-year survivors after TG still suffer from QoL inferiority from symptomatic and behavioral consequences of surgery, inferiority from behavioral consequences will persist even after symptomatic inferiority to STG survivors is no longer valid. Efforts to ameliorate persistent QoL inferiority in TG survivors should be directed toward restoring dietary behaviors, where TG survivors are prevented from enjoyable meals and social meals.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
66
0
3

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 83 publications
(79 citation statements)
references
References 39 publications
5
66
0
3
Order By: Relevance
“…Clinical features of PGS include the occurrence of various symptoms, reduced dietary intake, weight loss, reduced physical activity, and reduced physical and mental QOL. PGS is usually the most severe after TG, and the postoperative QOL of patients is known to be better after DG, in which the proximal stomach is partially preserved, than after TG[8,10,13,18,19]. Our study also showed a significantly higher “necessity for additional meals”, greater “weight loss”, lower “ability for working” and worse “dissatisfaction for daily life SS”, “PCS” and “MCS” of SF-8 in the TG group than in the DG group.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Clinical features of PGS include the occurrence of various symptoms, reduced dietary intake, weight loss, reduced physical activity, and reduced physical and mental QOL. PGS is usually the most severe after TG, and the postoperative QOL of patients is known to be better after DG, in which the proximal stomach is partially preserved, than after TG[8,10,13,18,19]. Our study also showed a significantly higher “necessity for additional meals”, greater “weight loss”, lower “ability for working” and worse “dissatisfaction for daily life SS”, “PCS” and “MCS” of SF-8 in the TG group than in the DG group.…”
Section: Discussionmentioning
confidence: 99%
“…For this purpose, existing general-purpose disease or symptom specific QOL questionnaires, such as GSRS[26,31,32], Gastrointestinal Quality of Life Index[12,33] and European Organization for Research and Treatment of Cancer Quality of Life Questionnaire; EORTC QLQ-C30 + QLQ-STO22[10,13,18,19,21,34-36], which were established for other purposes and had verified reliability and validity, have been mainly used, because there have been no established questionnaires specified for the postgastrectomy evaluation. However, these questionnaires are likely to be inadequate for the clinical evaluation of postgastrectomy patients, because they do not contain “dumping” and/or “meal-related distress”, which are symptoms that are well-recognized as significantly affecting the postoperative QOL of gastrectomy patients.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It was inevitable that TG procedure would yield worse complications such as oesophageal reflux, diarrhea, and nausea/vomiting because of a restricted food reservoir in the TG group. Lee SS regarded that survivors after TG exhibited ongoing QoL inferiority on various functional and symptom scales at postoperative five years, beyond that time, QoL inferiority of the TG to the DG group generally disappeared except of eating restrictions implicates[34]. It is possible that some form of gastric substitute, such as jejunal interposition, might also be helpful in reducing eating restrictions following TG in the longer term[38].…”
Section: Discussionmentioning
confidence: 99%
“…The incidence of metachronous lesions is one of the concerns after endoscopic resection as almost all the gastric mucosa is preserved. However, considering that total gastrectomy has a significantly negative impact on patient quality of life, the preservation of gastric function might outweigh the possible disease burden of metachronous recurrence [25]. Moreover, with scheduled surveillance endoscopy, metachronous lesions can be detected at an early stage and so can be suitable candidates for endoscopic resection [26].…”
Section: Data Represent the Number Of Patients (%) Or The Median (Intmentioning
confidence: 99%